Six Viable Readings from Isaiah 1–39 in the Great Isaiah Scroll (1QIsaa) - Flint, Peter (Théologiques, 2016)
In order to illustrate the contribution of the Great Isaiah Scroll from Qumran (1QIsaa) to textual criticism, this paper presents six viable readings for Isaiah 1–39, i.e. variants that most likely represent the original Hebrew text. In assessing the cases of Isaiah 3 : 24 ; 9 : 16 [English 9 : 17] ; 18 : 7 ; 19 : 18 ; 21 : 8 ; 23 : 10, the author takes into account the textual character of the manuscript, the scribal habits of the copyist, the work of scholars and commentaries on the Book of Isaiah, recent translations of Isaiah, as well as the context and the overall sense of the passage. In all six instances — with the possible exception of Isa 19 : 18 — the reading in 1QIsaa is found to be compelling. These readings and similar ones should therefore be included as part of the main text of Isaiah (not the apparatus) in future editions of the Hebrew Bible, and part of the main text of Isaiah in future translations (not the footnotes).